1998
DOI: 10.1046/j.1365-2141.1998.00842.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the PAX5/BSAP transcription factor in haematological tumour cells and further molecular characterization of the t(9;14)(p13;q32) translocation in B‐cell non‐Hodgkin's lymphoma

Abstract: Summary. The PAX5 gene encodes the BSAP (B-cell-specific activator protein) which is a key regulator of B-cell development and differentiation. A recurring translocation t(9;14)(p13;q32) in non-Hodgkin's lymphoma moves the PAX5 on 9p13 within close proximity of the immunoglobulin heavy chain gene (IGH). KIS-1 cell line was established from a patient with diffuse large cell lymphoma of B-cell type carrying t(9;14). We analysed PAX5/BSAP expression by Northern and Western blotting in a panel of haematological tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 40 publications
1
38
0
1
Order By: Relevance
“…The sensitivity of this nested PCR method, determined using the t(14;18)-positive lymphoma cell lines TK, 18 FL218, and FL318, 19 appeared to be approximately 1/10 6 cells, and was almost the same as that reported previously in studies of white individuals. [12][13][14][15][16][17] Statistical analysis between the 2 groups was performed using the 2 test.…”
Section: Methodssupporting
confidence: 60%
“…The sensitivity of this nested PCR method, determined using the t(14;18)-positive lymphoma cell lines TK, 18 FL218, and FL318, 19 appeared to be approximately 1/10 6 cells, and was almost the same as that reported previously in studies of white individuals. [12][13][14][15][16][17] Statistical analysis between the 2 groups was performed using the 2 test.…”
Section: Methodssupporting
confidence: 60%
“…BSAP/Pax5 is a transcription factor also necessary for early B cell development (68,69). It was observed that the BSAP/Pax5 gene was strongly expressed in B cell lymphomas through its translocation into Ig heavy chain locus (70,71). In addition, antisense oligonucleotide-mediated suppression of BSAP activity caused growth inhibition of B cells, but not of T lymphoma or plasma cell lines (72).…”
Section: Notch1 Inhibition Of B Cell Proliferation 36529mentioning
confidence: 99%
“…By definition, the World Health Organization criteria are stringent for the diagnosis of LPL, excluding plasmacytoid variants of other lymphomas. 9 The heterogeneity of lymphomas associated with t(9;14) is also illustrated by previous reports of sequenced PAX5 breakpoints as shown in Figure 1: a plasmacytoid small lymphocytic lymphoma (1052), 6 a splenic marginal zone lymphoma (MZL-1), 10 a diffuse large B-cell lymphoma (895), 8,11 ␣-heavy chain disease (MAL), 12,13 and the KIS-1 cell line. 4,5 Given the frequency of low-grade B-cell lymphomas other than LPL associated with t(9;14), we chose to investigate the incidence of the PAX5 gene rearrangement in a series of low-grade B-cell lymphomas with an emphasis on plasmacytic differentiation.…”
mentioning
confidence: 84%
“…6,7 Encoding B-cell-specific activator protein, a B-cell transcription factor, the PAX5 gene has been thought to contribute to the development of lymphoma when brought into close proximity of the IgH. 8 The incidence of this translocation has been cited in at least one textbook as involving ϳ50% of LPL, 9 when in fact only a small number of cases have been previously studied.…”
mentioning
confidence: 99%